The Phenomenon of Learning Social and Moral Skills on the Aggressive Behavior of Elementary School Students - Firmansyah, Farid; Suroso, Suroso; Farid, Muhammad (Formosa Journal of Multidisciplinary Research, 2024)
It is suspected that there has been aggression in the school environment, including at the elementary school level. Concrete efforts are needed to reduce aggression behavior in schools carried out by fellow students, because the impact of aggression behavior inflicts prolonged psychological trauma on victims of aggression. This type of research is quantitative research with a post-test only experiment design. The aggressiveness scale is used to measure aggression behavior that has met the item discrimination and reliability indexes. The research data were analyzed with the Mann-Whitney non-parametric test, resulting in significant differences in aggression behavior of group students who acquired character learning, social skills, and morals with control group students. The aggression behavior that acquired character learning, social and moral skills was lower than the aggression behavior of the control group students. These findings suggest that character learning, social and moral skills have an effect on students' aggression behavior.